Invasive Group B Streptococcal Infection with Toxic Shock-Like Syndrome in a Postsplenectomy Patient - Pradeep Kumar Mada; Gabriel Castano; Andrew Stevenson Joel Chandranesan (Case Reports in Infectious Diseases)
The incidence of invasive group B streptococcal disease (GBS) in nonpregnant population is increasing. As per the Centers for Disease Control and Prevention (CDC), there are 10 cases in every 100,000 nonpregnant adults each year, and 1 in 20 nonpregnant adults with serious GBS infections die. GBS infection is almost always associated with underlying risk factors such as diabetes mellitus or malignancy. We present a 47-year-old female with a remote history of splenectomy presented with toxic shock-like syndrome secondary to invasive GBS infection.